2022
DOI: 10.1021/acs.analchem.1c04368
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemiluminescence Resonance Energy Transfer System Based on Silver Metal–Organic Frameworks as a Double-Amplified Emitter for Sensitive Detection of miRNA-107

Abstract: As a class of electrochemiluminescence (ECL) enhancers, silver-based materials have broad application prospects. In this work, a novel silver metal–organic framework (AgMOF) was developed as a self-enhanced ECL emitter by one-step mixing and standing at room temperature. The AgMOF could produce strong and stable ECL emissions based on a double-amplification method, which originated from the aggregation-induced ECL emission of ligands and catalyzing S2O8 2– to produce more SO4 •– by silver. Moreover, an ECL res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Though some cationic MOF materials could be obtained at room temperature, it still retained the defect of long reaction time. [50,51] In this work, the crystal of Ag-TPPE was first prepared hydrothermally by reacting 1,1,2,2-tetrakis(4-pyridylphenyl)ethylene (TPPE) (Figure S1, Supporting Information) with AgNO 3 in mixed solvent of CH 3 CN/DMSO (v/v, 10/4) at 100 °C for 48 h (Figure S2a, Supporting Information). Single-crystal X-ray diffraction indicated that Ag-TPPE remained identical four-interpenetrated networks as coordination polymer obtained by diffusion method (Table S1, Supporting Information).…”
Section: Fast Synthesis At Room Temperature and Structure Of Ag-tppementioning
confidence: 99%
“…Though some cationic MOF materials could be obtained at room temperature, it still retained the defect of long reaction time. [50,51] In this work, the crystal of Ag-TPPE was first prepared hydrothermally by reacting 1,1,2,2-tetrakis(4-pyridylphenyl)ethylene (TPPE) (Figure S1, Supporting Information) with AgNO 3 in mixed solvent of CH 3 CN/DMSO (v/v, 10/4) at 100 °C for 48 h (Figure S2a, Supporting Information). Single-crystal X-ray diffraction indicated that Ag-TPPE remained identical four-interpenetrated networks as coordination polymer obtained by diffusion method (Table S1, Supporting Information).…”
Section: Fast Synthesis At Room Temperature and Structure Of Ag-tppementioning
confidence: 99%
“…One type of ECL-RET system consists of a nanomaterial luminophore and an organic (or inorganic) reagent as a donor/ acceptor pair. 124,125 As shown in Fig. 4A, Yang's group designed an ECL-RET system based on graphitic carbon nitride nanosheets (GCNNs) and Ru( phen) 3 2+ as a donor/ acceptor pairs, in which the signal was regulated by the amount Ru( phen) 3 2+ present.…”
Section: Nanomaterials As Luminophores For Amplified Ecl Biosensingmentioning
confidence: 99%
“…Electrochemiluminescence (ECL), a form of energy relaxation, was triggered by the electrochemical stimulation, which was attracting increasing interest in a variety of areas, such as clinical diagnosis, environmental regulation, food analysis, and drug detection on account of low background, high sensitivity, and excellent controllability. In the coreactant ECL system, the coreactant was indispensable to improve the ECL efficiency of the emitter. However, the reaction between the external coreactant and emitter in the traditional coreactant ECL system had certain disadvantages of slow electron transfer speed and low ECL efficiency, limiting the improvement of ECL strength. , Therefore, it was particularly important to explore an efficient ECL emitter to avoid the electron transmission obstruction and large energy loss between the emitter and coreactant in solution. On account of the π–π stacking and electrostatic interactions as well as the stimulation of electrical activity by heteropolar B–N bonding, boron carbon nitride nanosheets (BCN NSs) exhibited striking performance such as extraordinary chemical stability, excellent adsorption, and impressive oxygen reduction reaction catalysis. Moreover, the electronic tunneling among the ultrathin BCN NSs’ interlamination could realize faster electron transfer, which was conducive to the rapid and effective intramolecular reaction.…”
Section: Introductionmentioning
confidence: 99%